Analisis Pengaruh Tekanan Mesin Ekstruder terhadap Kuat Tekan Hasil Produk Bata Merah - Sendi Ariyandi (Sekolah Tinggi Teknologi Wastukancana, 2026)
This study was conducted to analyze the performance of the ekstruder machine on the production quantity and quality of the bricks produced. This aims to produce brick products with compressive strength according to standards. Experiments were conducted at three different pressures at (60; 65; 70) Psi for two samples of red bricks, namely before being burned and after being burned. The analysis shows that for the machine transmission using a type B belt with a belt circumference of 1063.622 mm, so that the V belt used by the motor is a nominal belt number 41 inches. From the results of data processing for linear regression of red bricks before being burned with a correlation value of 98.7%, it can be categorized as very strong. The linear regression of red bricks before being burned is 0.10 while alpha < 0.05 so it can be concluded that there is no significant influence on variable X with Y. The linear regression of red bricks after being burned is 0.07 while alpha < 0.05 so it can be concluded that there is no significant influence on variable X with Y. The research results obtained show that the smaller the vacuum pressure on the brick, the better the density and compression results obtained, whereas conversely the greater the vacuum pressure, the less good the results of the density and compression test results of the red brick, this occurs both in red bricks that have not been burned and those that have been burned.